Dissociating Higher and Lower Order Visual Motion Systems by Priming Illusory Apparent Motion. (January 2018) - Heller, Nathan H.; Davidenko, Nicolas
Motion processing is thought of as a hierarchical system composed of higher and lower order components. Past research has shown that these components can be dissociated using motion priming paradigms in which the lower order system produces negative priming while the higher order system produces positive priming. By manipulating various stimulus parameters, researchers have probed these two systems using bistable test stimuli that permit only two motion interpretations. Here we employ maximally ambiguous test stimuli composed of randomly refreshing pixels in a task that allows observers to report more than just two types of motion percepts. We show that even with such stimuli, motion priming can constrain the unstructured random pixel patterns into coherent percepts of positive or negative apparent motion. Moreover, we find that the higher order system is uniquely susceptible to cognitive influences, as evidenced by a significant suppression of positive priming in the presence of alternative response options.